Health knowledge of rural Bangladeshi children: does BRAC's non-formal schools make any impact? - Nath, Samir R. (BRAC Research and Evaluation Division (RED), 2019)
This report explores the impact of BRAC's Non-Fonnal Primary Education Programme (NFPE} on raising health knowledge of the rural Bangladeshi children. Three groups of children viz. NFPE graduates, formal school learners and children who never went to school were assessed an instrument containing six health knowledge items. A sample of 720 children, equally distributed by study groups and sex, were selected randomly. Data were collected from five areas where a surveillance system was in operation. This study reveals that NFPE graduates are more likely to have higher level of health knowledge than the children of other two groups. The impact of NFPE is due to its extra emphasis to enhance positive influence of education on lives of the rural population.